A history of women in mathematics - DeBakcsy, Dale. (Philadelphia)
xi, 200 sayfa, [8] sayfa portre
Keywords: “From ancient Greece to medieval Baghdad, from Revolutionary France to China's Qing Dynasty, women mathematicians have worked alongside men to a degree that was denied them in most other fields of scientific inquiry. Locked out of biological studies first by restrictions on their freedom of travel and later because of concerns that they would be corrupted by evolutionary thought, effectively barred from experimental physics for centuries through lack of access to specialized equipment, and inconsistently permitted a medical education, women have, for three thousand years and more, been a steady presence during every great mathematical era. They have contributed to the fundamentals of geometry and the expansion of algebra from the earliest days of those disciplines, and stepped in, on multiple occasions, to save the mathematical traditions of their home countries from death by ossification. They have guided us through the twisted realms of non-Euclidean space, gifted us the mathematical models we need to understand the behavior of the metals of our buildings and the soils we construct them upon, and given us an at times chilling view into the fates of super-massive systems over deep time. A History of Women in Mathematics, the first comprehensive account of women's role in mathematics in 35 years, tells the stories of over a hundred women, some of whom had to go to the lengths of lying about their gender in correspondence, or secrete themselves behind screens during lectures to access the mathematical resources that their male counterparts took for granted, but many of whom had positions of academic honor and international prestige that women in other fields would have to wait centuries to attain. From Theano of Croton to Rachel Riley, here are the tales of the women who have illuminated and demystified the profound structures upon which our reality is built, with stones of number and mortar of imagination.“ --